1998
DOI: 10.1111/j.1945-5100.1998.tb01717.x
|View full text |Cite
|
Sign up to set email alerts
|

The condensation with partial isolation (CWPI) model of condensation in the solar nebula

Abstract: Abstract-We have developed a nebular condensation model and a computational routine that potentially can account for the unequilibrated mineral assemblages in chondritic meteorites. The model assumes that as condensation proceeds, a specified fraction (called the isolation degree, 6) of the existing condensate is steadily withdrawn from reactive contact with the residual gas, presumably as a result of the growth and aggregation of condensed mineral grains. The isolated condensates may remain in the condensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(115 citation statements)
references
References 21 publications
6
108
1
Order By: Relevance
“…The required fractionation could have resulted from condensation with partial isolation (Petaev and Wood 1998) or from partial evaporation during chondrule formation.…”
Section: Fractionation Of Common and Moderately Volatile Elements Durmentioning
confidence: 99%
See 1 more Smart Citation
“…The required fractionation could have resulted from condensation with partial isolation (Petaev and Wood 1998) or from partial evaporation during chondrule formation.…”
Section: Fractionation Of Common and Moderately Volatile Elements Durmentioning
confidence: 99%
“…16) is difficult to explain by equilibrium condensation from a gas of solar composition. Equilibrium condensation calculations for a gas of solar composition, which is characterized by an atomic Si/Mg ratio of ~1 (Anders and Grevesse 1989), do not predict condensation of silica at any values of dust/gas ratio or total pressure (e.g., Grossman 1972; Petaev and Wood 1998;Ebel and Grossman 2000). Instead, the last silicate condensate is enstatite that forms either by reaction between SiO (gas) and forsterite or by reaction between SiO (gas) and forsterite + melt, depending on the total pressure and dust/gas ratio (Petaev and Wood 1998;Ebel and Grossman 2000).…”
Section: Fractionation Of Common and Moderately Volatile Elements Durmentioning
confidence: 99%
“…Larimer and Wasson (1988) concluded that the enstatite chondrites (EH and EL combined) had lost -58% of their solar complement of Al and Ca, 51% of their solar Mg, and 33% of their solar Si in a "refractory element" fractionation. Petaev and Wood (1998) reported that partial isolation of a refractory component over a range of temperatures produced minerals such as silica polymorph, oldhamite, Na-sulfides, metal, troilite, and enstatite, most of which are found in enstatite chondrites. Modal abundances were not given, but Petaev and Wood (1998) stated that "the matches between calculated and real mineralogies.. .…”
Section: Refractory Element Fractionationmentioning
confidence: 99%
“…Petaev and Wood (1998) reported that partial isolation of a refractory component over a range of temperatures produced minerals such as silica polymorph, oldhamite, Na-sulfides, metal, troilite, and enstatite, most of which are found in enstatite chondrites. Modal abundances were not given, but Petaev and Wood (1998) stated that "the matches between calculated and real mineralogies.. . are not perfect.…”
Section: Refractory Element Fractionationmentioning
confidence: 99%
See 1 more Smart Citation